The efficacy of paradigmatic intersections between inclusive development and the feminisation of poverty - Sulikah Asmorowati; Violeta Schubert (Faculty of Social and Political Science, Universitas Airlangga, 2018)
This paper explores the paradigmatic intersections between ‘inclusive development’ and the ‘feminisation of poverty’. Intersections are typical in the development subject, with the extent of the efficacy of inclusive development enabling opportunities addressing gender equality. In the emergent synthesis of inclusive (economic) growth and strategies for poverty alleviation, the challenges and opportunities associated with the paradigmatic shifts are evident. This is the case in the programs that are directed at the women household heads, such as Program Penanggulangan Feminisisasi Kemiskinan or the Feminisation of Poverty Alleviation Program (PFK) in East Java. This paper is based on the research on the implementation of PFK in the Regions of Trenggalek, Lamongan, Nganjuk and Banyuwangi. It highlights the importance of delving deeper into the processes involved and how the program has facilitated economic empowerment through entrepreneurship. Using qualitative research methods involving observation, analysis of relevant documents, and interview with a total of 98 informants, this research finds that in targeting the women household heads as its beneficiaries, the PFK has enabled unforeseen gains in terms of giving a voice to women and heralding a change in their participation and inclusion in relation to community issues and activities. This research also finds that, there is the challenges associated with program’s sustainability. In this, we conclude that, the issue of whether a one-oﬀ cash transfer, though guided, can serve as an impetus for women to lift themselves out of poverty is dependent on a number of factors that requires a more holistic approach to the sustainable capacity of development and mentorship.